Rethinking the education of retail design. What are the competences a retail designer needs in this fast evolving discipline?. (28th July 2017) - Quartier, Katelijn; Claes, Stephanie; Vanrie, Jan
Abstract: It has been our hypothesis that designing for retail in the future would strongly benefit from more specialized education and training programs, truly integrating social sciences and design disciplines. To this end, we are currently aiming to launch a postgraduate certificate program on retail design. In preparing this program, we have critically reviewed the three different educational programs that we already organize on retail design.To have a first indication of the validity of this approach, we were able to use interviews with senior and junior designers of 10 retail design agencies. The results suggest that there seems to be both a demand and an opportunity for a retail design program for (young) professionals who will work together in group on a (preferably realistic) design assignment, which offers a sufficiently deep handling of issues, an integration of theory and practice via a work-shop set-up and should most likely be offered in English.